The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5455/faa.277539
|View full text |Cite
|
Sign up to set email alerts
|

An overview of diseases in fish hatcheries and nurseries

Abstract: Quality and healthy fish seed is the prerequisite for sustainable aquaculture. A major challenge to the expansion of aquaculture production is the outbreak of diseases. Disease induced mortality is a serious issue for the fish seed industry. The immature immune system in fish makes the early developmental stages more susceptible to infectious diseases. Common fish diseases in hatcheries and in early rearing systems are caused by protozoan, ciliates, myxosporodians, worms, opportunistic bacteria and fungi. Prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…Fry are collected and transferred to tanks or hapas until they reach fingerling size. Infectious diseases are a major issue in hatcheries and can lead to massive mortality in larval populations 113 . For example, the majority of parasitic infections in tilapia occur during the early life stages of the fish; therefore, special attention should be paid to the prevention and treatment of parasites in hatcheries.…”
Section: Implementing Biosecurity Measures In the Value Chainmentioning
confidence: 99%
“…Fry are collected and transferred to tanks or hapas until they reach fingerling size. Infectious diseases are a major issue in hatcheries and can lead to massive mortality in larval populations 113 . For example, the majority of parasitic infections in tilapia occur during the early life stages of the fish; therefore, special attention should be paid to the prevention and treatment of parasites in hatcheries.…”
Section: Implementing Biosecurity Measures In the Value Chainmentioning
confidence: 99%
“…Potongkam and Miller (2006) reported that the catfish survival % during the first nursery phase was very low (40–50 %) compared to the second nursery phase (60–70 %). Furthermore, seeds from non-pathogen-free hatcheries or nurseries could be infected and transfer pathogens to the grow-out systems where disease can lead to high mortality rates ( Faruk and Anka, 2017 ; Hasan et al, 2020 ; Hasan and Haque, 2020 ). This poor survival greatly affects the availability of fries that can be used to stock grow-out ponds and consequently farmers profitability ( Ansa, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…This poor survival greatly affects the availability of fries that can be used to stock grow-out ponds and consequently farmers profitability ( Ansa, 2014 ). The main reason for the high mortality is the immature immune system, which makes the early developmental stages more susceptible to infectious diseases and mortality ( Chaput et al, 2020 ; Faruk and Anka, 2017 ). Farmers usually use antibiotics as a prophylactic measure to control the mortality of pangasius fries during the nursing phase, but the use of antibiotics has been discouraged after the spread of antimicrobial resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable fishery management depends on rearing the fish in appropriate conditions and improving successful preventive health care (Li et al., ). In this respect, fish should be raised using good management practices, especially at the yolk sac stage, at start of feeding and at the fry stage (Faruk & Anka, ). The intensive production of rainbow trout has resulted in increased health problems and economic losses related to diseases.…”
Section: Introductionmentioning
confidence: 99%